Association of Preoperative Opioid Use With Complication Rates and Resource Use in Patients Undergoing Hip Arthroscopy for Femoroacetabular Impingement. Issue 11 (19th November 2021) - Nazzal, Ehab M.; Wilson, Jacob M.; Farley, Kevin X.; Schwartz, Andrew M.; Xerogeanes, John W.
Background: Preoperative opioid use has been shown to be a negative predictor of patient outcomes, complication rates, and resource utilization in a variety of different orthopaedic procedures. To date, there are no studies investigating its effect on outcomes after hip arthroscopy in the setting of femoroacetabular impingement (FAI). Purpose: To determine the association of preoperative opioid use with postoperative outcomes after hip arthroscopy in patients with FAI. Study Design: Cohort study; Level of evidence, 3. Methods: The Truven Health MarketScan Commercial Claims and Encounters Database was queried for all patients who underwent hip arthroscopy for FAI between 2011 and 2018. Opioid prescriptions filled in the 6 months preceding surgery were queried, and the average daily oral morphine equivalents (OMEs) in this period were computed for each patient. Patients were divided into 4 cohorts: opioid naïve, <1 OME per day, 1 to 5 OMEs per day, and >5 OMEs per day. Postoperative 90-day complications, health care utilization, perioperative costs, postoperative opioid use, and 1- and 3-year revision rates were then compared among cohorts. Results: A total of 22, 124 patients were ultimately included in this study; 31.2% of these patients were prescribed opioids preoperatively. Overall, the percentage of preoperative opioid-naïve patients increased from 64.5% in 2011 to 78.9% in 2018. Patients who received preoperative opioids had a higher rate of complications, increased resource utilization, and increased revision rates. Specifically, on multivariate analysis, patients taking >5 OMEs per day (compared with patients who were preoperatively opioid naïve) had increased odds of a postoperative emergency department visit (Odds Ratio, 2.23; 95% confidence interval [CI], 1.94-2.56; P < .001), 90-day readmission (OR, 2.25; 95% CI, 1.77-2.87; P < .001), increased acute postoperative opioid use (OR, 25.56; 95% CI, 22.98-28.43; P < .001), prolonged opioid use (OR, 10.45; 95% CI, 8.92-12.25; P < .001), and 3-year revision surgery (OR, 2.14; 95% CI, 1.36-3.36; P < .001). Perioperative adjusted costs were increased for all preoperative opioid users and were highest for the >5 OMEs per day cohort ($6255; 95% CI, $5143-$7368). Conclusion: A large number of patients with FAI are prescribed opioids before undergoing hip arthroscopy, and use of these pain medications is associated with increased health care utilization, increased costs, prolonged opioid use, and early revision surgery.